Three Faces of the Rohingya Crisis: Religious Nationalism, Asian Islamophobia, and Delegitimizing Citizenship - Imtiyaz Yusuf (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2018)
Myanmar is a non-secular Buddhist majority country born out of the ashes of the murder of their leader of independence struggle, General Aung San, was assassinated on July 19, 1947, a few months before the independence of Burma on January 4, 1948. His failed legacy in integrating Myanmar into a multicultural nation which contains of Burmans as ethnic majority and non-Burman minorities continues to obsess Myanmar’s people. The Rohingya crisis is not a religious conflict between Islam and Buddhism because both of them have a long-shared history of peaceful coexistence. Furthermore, it is also not only a case of Buddhist persecution against Muslims as recognized by the Rohingyan nationalists. Actually, it is a clash between two views of nationalism over the claim to Myanmar citizenship. The conflict invokes Buddhist and Muslim nationalist in order to protect and preserve national ethnicities as religious identities in turn causing the rise of the new phenomena of Asian Islamophobia.